Green derived zinc oxide (ZnO) for the degradation of dyes from wastewater and their antimicrobial activity: a review - Mahlaule-Glory, Louisah M.; Hintsho-Mbita, Nomso C. (MDPI, 2022)
The quest for eco-friendly synthetic routes that can be used for the development of multifunctional materials, in particular for water treatment, has reinforced the use of plant extracts as replacement solvents in their use as reducing and capping agents during the synthesis of green derived materials. Amongst the various nanoparticles, Zinc Oxide (ZnO) has emerged as one of the preferred candidates for photocatalysis due to its optical properties. Moreover, ZnO has also been reported to possess antimicrobial properties against various bacterial strains such as E. coli and S. aureus. In this review, various types of pollutants including organic dyes and natural pollutants are discussed. The treatment methods that are used to purify wastewater with their limitations are highlighted. The distinguishing properties of ZnO are clearly outlined and defined, not to mention the performance of ZnO as a green derived photocatalyst and an antimicrobial agent, as well. Lastly, an overview is given of the challenges and possible further perspectives
Journal article published in Catalysts 2022, 12, 833.
Keywords: ZnO; Organic dyes; Photocatalytic activity; Antimicrobial analysis; Water-supply; Water -- Distribution; Water -- Pollution; Water -- Purification; Zinc oxide [